Strontium doping in mullite-type bismuth aluminate: a vacancy investigation using neutrons, photons and electrons - Gesing, Thorsten M. (2012)
We report on strontium doped dibismuth-nonaoxoaluminate(III) produced at 1023 K. Partial substitution of bismuth by strontium in the structure yields oxygen vacancies for charge balance.Introducing oxygen vacancies rearranged the associated Al2O7 double-tetrahedra forming ??Al3O10?? tri-clusters which were identified by multi-quantum 27Al MAS NMR. Both STEM-EDX and XPS showed homogeneous distribution of strontium in the bulk and on the surface, respectively. Moreover, XPS confirms the valence state of bismuth after doping. The orientations of bismuth 6s2 lone electron pairs were calculated using DFT methods. The amount of strontium in the crystal structure was further confirmed from the decomposition product SrAl12O19 formed during the temperature-dependent X-ray powder diffraction. The structural proof was carried out by refining the structure of (Bi0.94Sr0.06)2Al4O8.94 from powder neutron and X-ray diffraction data. Rietveld refinements clearly showed the under occupation of one oxygen site and the shift of two aluminum atoms from the doubletetrahedra to two tri-cluster sites.